Оцінювання якості виробництва виробів кондитерських пряникових - Козлов, Ю. В.; Молчанова, А. Р. (ХНУРЕ, 2025)
The work assessed the quality of confectionery production using the methods of a checklist, a quality histogram, and a cause-and-effect diagram (Ishikawa diagram). Based on the analysis, measures were proposed to improve product quality. The analysis also revealed that the biggest problem is controlling the level of fat content.
Keywords: кондитерський вироб; оцінювання якості виробництва